The Impact of Policies under Two Regimes: A Spatial Analysis of Stunting Density in Indonesia Using Geographically Weighted Regression (GWR) - Nabil Naufal; Mardatunnisa Isnaini; Nisa Nur Aisyah; Salshabila Shafa; Andi Illa Erviani Nensi; Muhammad Nur Aidi (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Stunting remains a significant public health challenge in Indonesia, despite a decline in prevalence over the past few years. This study aims to analyze changes in the spatial pattern of stunting density in 2013 and 2018 and identify the influencing factors using Geographically Weighted Regression (GWR). The study focuses on differences in health policy approaches between the administrations of President Susilo Bambang Yudhoyono (SBY) and President Joko Widodo (Jokowi). Data were obtained from the Indonesian Basic Health Research (Riskesdas) and the Indonesia Nutrition Status Survey (SSGI), with social, economic, and health-related variables as predictors. The findings indicate that factors such as the frequency of neonatal visits and access to safe drinking water are significantly associated with stunting prevalence across different regions. Furthermore, the declining influence of maternal Chronic Energy Deficiency (CED) in 2018 reflects a shift in policy priorities from SBY's programmatic approach to Jokowi's infrastructure-based strategy. These results highlight the need for geographically targeted health policies to ensure more effective interventions in reducing stunting rates in Indonesia.
Keywords: Stunting; Geographically Weighted Regression; Nutrition Policy; Spatial Analysis; Health Politics